Biocompatible chicken bone extracted dahllite/hydroxyapatite/collagen filler based polysulfone membrane for dialysis. Issue 1 (January 2022) - Zaman, Shafiq Uz; Zaman, Muhammad Khaliq U; Irfan, Muhammad; Rafiq, Sikander; Irfan, Masooma; Muhammad, Nawshad; Saif-ur-Rehman,; Wajeeh, Salman; Naz, Gul
In the current study, dahllite/hydroxyapatite/collagen filler extracted via calcination of wasted chicken bone was blended with PSf polymer to obtain highly biocompatible, and antifoulant hemodialysis membranes. FTIR and Raman spectroscopic analysis was done to obtain information about the bonding chemistry of the obtained filler. The intermolecular interaction that existed between dahllite/hydroxyapatite/collagen filler and pristine PSf was confirmed by Raman spectroscopic study. The PSf polymer exhibited a sponge-like structure owing to its high thickness and slow exchange with non-solvent in coagulation bath whilst the instantaneous de-mixing course produced finger-like capillaries in dahllite/hydroxyapatite/collagen filler based PSf membranes as exposed by SEM photographs. The presence of different wt. % of filler composition in the PSf matrix improved the mechanical strength as revealed by fatigue analysis. The hydrophilic character improved by 78% while leaching consistency adjusted to 0%–4%. Pure water permeation (PWP) flux improved by nine times. The pore profile improved with the addition of filler as revealed by hydrophilicity experiment, PWP flux, and SEM micrographs. Fouling evaluation results disclosed that filler based membranes showed 36% less adsorption of protein (BSA) solution together with more than 84% flux recovery ratio. The biocompatibility valuation analysis unveiled that membranes composed of filler showed extended prothrombin and thrombin coagulation times, reduced activation of fibrinogen mass, and less adhesion of plasma proteins in comparison with pristine PSf membrane. The adsorption capacity of fabricated membranes for urea and creatinine improved by 31% (in the case of urea) and 34% (in the case of creatinine) in contrast with pristine PSf membrane. The overall results showed that the M-3 membrane was optimized in terms of surface properties, protein adhesion, anticoagulation activity, and adsorption amount of urea and creatinine.